Community engagement in TB care - Getahun, Haileyesus (Henry Stewart Talks, 2013)
Community based TB activities, Community health workers and volunteers, Evolution in the global response, Community TB care in Africa project, Cost effectiveness, Asian perspective, Latin American perspective, Global policy and programme guidance, Monitoring of community based TB activities, Funding to NGOs and community groups, Little interaction with NTPs